Effects of Salinity and Concentration of ACC-deaminase PGPR from Bidara Root on Chili Growth and Yield - Naja, Baiq Safinatun; Nikmatullah, Aluh; Ernawati, Ni Made Laksmi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Soil salinity is an escalating challenge in dryland agriculture, where rising electrical conductivity disrupts water balance and nutrient uptake. These stresses stimulate excessive ethylene production, which suppresses root growth and reduces overall plant vigor. Plant growth–promoting rhizobacteria (PGPR) with ACC deaminase activity offer a promising mitigation strategy by degrading ACC, the ethylene precursor, thereby helping plants maintain growth under saline conditions. This study evaluated the effect of different concentrations of ACC deaminase producing bacteria isolated from Bidara (Ziziphus mauritiana Lam.) roots on chili (Capsicum annum L.) growth under graded salinity stress. Bacterial cultures were harvested at OD₆₀₀ = 0.8 and applied at three concentrations (0, 10, and 20 mL/L) to chili seedlings exposed to four salinity levels (0, 2, 4, and 8 dS/m). Growth parameters—including plant height, leaf number, biomass, and root development—were measured to assess physiological responses. Results showed that increasing salinity progressively reduced plant growth, with substantial inhibition observed at 8 dS/m. In contrast, bacterial application significantly improved plant performance across all salinity levels, and the 20 mL/L concentration consistently produced the greatest enhancement. The improved growth is attributed to enhanced root system function and chlorophyl concentration. These findings highlight the essential role of ACC deaminase producing bacteria in mitigating salinity stress in chili cultivation under dryland conditions and underscore the importance of optimizing bacterial concentration to maximize their beneficial effects.